A large-scale national study of gambling severity among immigrant and non-immigrant adolescents: The role of the family. (March 2017) - Canale, Natale; Vieno, Alessio; Griffiths, Mark D; Borraccino, Alberto; Lazzeri, Giacomo; Charrier, Lorena; Lemma, Patrizia; Dalmasso, Paola; Santinello, Massimo
Abstract: Aim: The primary aim of the present study was to examine the association between immigrant generation, family sociodemographic characteristics, and problem gambling severity in a large-scale nationally representative sample of Italian youth. Method: Data from the 2013–2014 Health Behaviour in School-aged Children (HBSC) Survey were used for cross-sectional analyses of adolescent problem gambling. Self-administered questionnaires were completed by a representative sample of 20, 791 15-year-old students. Respondents' problem gambling severity, immigrant status, family characteristics (family structure, family affluence, perceived family support) and socio-demographic characteristics were individually assessed. Findings: Rates of adolescent at-risk/problem gambling were twice as high among first generation immigrants than non-immigrant students; the odds of being at-risk/problem gamblers were higher among first-generation immigrants than adolescents of other immigrant generations or non-immigrant. Not living with two biological or adoptive parents appears to be a factor that increases the risk of becoming a problem gambler in first generation immigrants. Conclusions: Immigrant status and family characteristics may play a key role in contributing to adolescent problem gambling. Highlights: Little is known about the link between immigrations status and adolescent gambling. This study used a large-scale nationally representative youth sample. First-generation immigrants had higher gambling severity. There was an interaction between family structure and first-generation immigrants. Not living with two parents increase gambling severity in first-generation immigrants.